MODEL PENGEMBANGAN EKONOMI KREATIF DALAM MENGAKSELERASI PEMBANGUNAN PARIWISATA KAWASAN LASAKOSA KABUPATEN BIMA - Tauhid - Tauhid (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2022)
The Lambu, Sape, Komodo and Sangiang (LASAKOSA) area is an area that has tourism potential such as the natural and cultural potential of the Bima community, which encourages the acceleration of creative economic development in order to reduce poverty, expand employment opportunities, grow MSMEs and form a community that cares about tourism. . This study aims to determine: (1) the potential for tourism and the creative economy, (2) the creative economy development model in accelerating tourism development in the LASAKOSA area. Data sources: (1). Informants who master the problems studied. and (2). Research-appropriate documents. Data analysis techniques are descriptive qualitative and SWOT. The results showed that: first; based on a SWOT analysis creative economy development in the tourism development of the LASAKOSA area has strengths, weaknesses, opportunities and threats. And second; the model formulated is the creative economy "UMA" development model in accelerating tourism development in the Lasakosa area. In this model there are two main foundations, namely first, the potential of Natural Resources and Tourist Attractions and secondly the potential of Human Resources. and supported by the government's role in regional development, there are supporting pillars of the creative economy "UMA" development model, namely: the tourism industry, local institutions, technology, scholar groups, and financial institutions